Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.ajpath.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

ProNGF Correlates with Gleason Score and Is a Potential Driver of Nerve Infiltration in Prostate Cancer

Abstract: Nerve infiltration is essential to prostate cancer progression, but the mechanism by which nerves are attracted to prostate tumors remains unknown. We report that the precursor of nerve growth factor (proNGF) is overexpressed in prostate cancer and involved in the ability of prostate cancer cells to induce axonogenesis. A series of 120 prostate cancer and benign prostate hyperplasia (BPH) samples were analyzed by IHC for proNGF. ProNGF was mainly localized in the cytoplasm of epithelial cells, with marked expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 20 publications
3
107
0
Order By: Relevance
“…ProNGF was correlated to tumor aggressiveness and low-risk tumors (Gleason score ¼ 6) contained significantly less proNGF than intermediate and high-risk tumors (Gleason score 7). Interestingly, although at this stage, there are no supporting mechanistic animal studies, prostate cancer cells in vitro were found able to stimulate neuron outgrowth through the secretion of proNGF (14). Whether or not proNGF acts directly on neurons, or is first processed into NGF, is still to be determined, but this study showed that proNGF/NGFs are involved in the neurogenic ability of prostate cancer cells.…”
Section: Neurogenic Activity Of Tumor Cells: the Role Of Neurotrophicmentioning
confidence: 79%
See 2 more Smart Citations
“…ProNGF was correlated to tumor aggressiveness and low-risk tumors (Gleason score ¼ 6) contained significantly less proNGF than intermediate and high-risk tumors (Gleason score 7). Interestingly, although at this stage, there are no supporting mechanistic animal studies, prostate cancer cells in vitro were found able to stimulate neuron outgrowth through the secretion of proNGF (14). Whether or not proNGF acts directly on neurons, or is first processed into NGF, is still to be determined, but this study showed that proNGF/NGFs are involved in the neurogenic ability of prostate cancer cells.…”
Section: Neurogenic Activity Of Tumor Cells: the Role Of Neurotrophicmentioning
confidence: 79%
“…Whether or not proNGF acts directly on neurons, or is first processed into NGF, is still to be determined, but this study showed that proNGF/NGFs are involved in the neurogenic ability of prostate cancer cells. ProNGF/NGFs have been shown to be involved in perineural invasion (5), and the study by Pundavela and colleagues (14) indicates that these growth factors also participate in tumor neoneurogenesis. Another investigation by Dobrenis and colleagues (15) has shown that the hematopoietic growth factor G-CSF constrains the growth of prostate cancer cells by supporting the survival of sympathetic nerve fibers.…”
Section: Neurogenic Activity Of Tumor Cells: the Role Of Neurotrophicmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported the ability of cancer cells to attract nerve fibers (40,41), very few have reported the impact of stromal cells in this process (12), especially in PDA where stromal cells compose the vast majority of the tumor cell mass. Therefore, our goal was to identify molecular targets from the PDA microenvironment that are involved in PANR, which may lead to the discovery of potent future adjuvant therapies that could prolong survival and reduce morbidity by blocking PANR.…”
Section: Discussionmentioning
confidence: 99%
“…It had already been reported (Delsite and Djakiew, 1999) that a proNGF molecule of 22 kDa is expressed by human prostatic stromal cells, as detected immunologically, but mature NGF, which would be expected to be the agent capable of attracting sympathetic and/or sensory neurites was not detected in these studies. To address whether NGF or proNGF may be involved in prostate tumor-directed neurogenesis, a cohort of 120 human prostate samples was examined by immunohistochemistry (Pundavela et al ., 2014). ProNGF was readily detected in the cytoplasm of the cancer cells but much less so in the stromal cells.…”
Section: Neurotrophin-induced Neurogenesis In Tumor Tissuesmentioning
confidence: 99%